FUNCTION OF CELLULAR IMMUNE FACTORS - Panjieva Almira,; Umarova Tamila Abdufattoevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Introduction. Cellular immunity is mediated by cells of both specific and nonspecific defense: specific cells include helper T lymphocytes (CD4+) and cytotoxic “killer” T lymphocytes (CD8+), which are highly specialized for destroying virions as well as virus-infected cells. Nonspecific cells include macrophages and NK cells. The function of cellular immune factors is associated with suppression of viral replication, migration, and retention of macrophages, lymphocytes, and inflammatory cells at the site of infection.